Choosing between Patient Care Needs and Accurate Data Capture: Exploring Nurses' Experiences of Excessive Documentation Burden - Thate, Jennifer; Lee, Rachel Y.; Mugoya, Rosemary; Diamond, Courtney J.; Daramola, Temiloluwa; Yen, Po-Yin; Rossetti, Sarah C. (Applied Clinical Informatics, 2025)
This study aimed to explore: (1) how nurses in the acute care setting describe their experience(s) of excessive documentation burden (ExDocBurden); (2) what factors contribute to ExDocBurden for nurses in the inpatient setting; and (3) nurses' perspectives on solutions to mitigate ExDocBurden that support documentation practices that they deem essential to providing safe, high-quality care.Semistructured interviews were conducted with 18 acute care nurses. Transcribed interviews were analyzed using the constant comparative method.All sources of ExDocBurden were categorized as issues of usability which included four themes: (1) inaccurate data resulting from EHR rules or logic that force or limit responses; (2) burdensome lengthy flowsheets—scrolling, clicking, and searching for the right place to document; (3) checking the box prevents meaningful information capture; and (4) a moving target—ongoing updates and inadequate training. Strategies to reduce ExDocBurden were categorized as “current approaches” and “future innovations.”Based on synthesis of categories and themes, alongside existing literature, we propose the following recommendations: (1) develop evidence-based consensus on essential EHR data elements, (2) minimize structured data entry interfaces and maximize forms of data entry that develop and reflect nurses' clinical reasoning, (4) leverage emerging technologies to capture and parse data into structured formats suitable for secondary uses.Addressing usability issues identified by nurses is critical to reducing ExDocBurden. Increasing required data entry in structured flowsheets not only contributes to ExDocBurden, but also leads to inaccurate data capture that has serious implications for AI tools that rely on the quality of previously documented data.
Keywords: electronic health record; excessive documentation burden; nursing documentation